An illustrated case for unemployment insurance reform - Christopher J. O'Leary; Stephen A. Wandner (W.E. Upjohn Institute for Employment Research, 2020)
We present a graphic case for unemployment insurance (UI) program reform. Through a series of illustrations summarizing historical trends, we show how the UI system has diverged from its intended purposes. Our figures show the decline of the program in addressing its essential aims of paying adequate unemployment compensation during involuntary unemployment and providing reemployment services. We illustrate the big differences in UI programs that have emerged because of the broad discretion afforded states to determine benefit generosity. We also illustrate declines in the financial means for providing benefits and reemployment services and a widening divergence among states in the quality of UI programs. Our concluding section presents a list of reforms that would restore UI as a pillar of social insurance and the labor market.
Keywords: J65; H71; J68; 330; unemployment insurance; benefit eligibility; benefit adequacy; wage replacement ratio; recipiency rate; forward funding; taxable wage base; experience rating; reemployment services; program administration